Listening to The Intrepid Alix: audio experience of a classical bande dessinée - Benoît Glaude (Comicalités, 2023)
Although digitization and transmedia storytelling broaden our sensory experience of comics nowadays, adaptation and merchandising have long been offered similar opportunities. As Ian Hague’s book Comics and the Senses has pointed out, admitting the obviousness that “materiality matters” implies “challenging the idea that comics are a purely visual medium.” Engaging Hague’s proposition, this article focuses on a “Disque d’aventure” produced by Festival, a French record label, in 1960: Alix l’intrépide. The first episode in the French-language comics series Alix by Jacques Martin, The Intrepid Alix, had been serialized in Tintin magazine (1948-49), then released as a comics album (1956), before being adapted by Jean Maurel into an audiobook on LP vinyl record (1960). As a first step towards a multisensory approach to comics, this article deals with the sound dimension of the comic strip and the audiobook. Analysis of the record broadens our understanding of the audio experience of The Intrepid Alix. However, we will see that it cannot be considered simply as a soundtrack to the comic. Indeed, I will demonstrate that The Intrepid Alix does not need an audiobook edition in order to integrate a sound experience.